Increased generation of Foxp3(+) regulatory T cells by manipulating antigen presentation in the thymus. - Lin, J; Yang, L; Silva, H; Trzeciak, A; Choi, Y; Schwab, S; Dustin, M; Lafaille, J (Nature Publishing Group, 2016)
Regulatory T-cell (Treg) selection in the thymus is essential to prevent autoimmune diseases. Although important rules for Treg selection have been established, there is controversy regarding the degree of self-reactivity displayed by T-cell receptors expressed by Treg cells. In this study we have developed a model of autoimmune skin inflammation, to determine key parameters in the generation of skin-reactive Treg cells in the thymus (tTreg). tTreg development is predominantly AIRE dependent, with an AIRE-independent component. Without the knowledge of antigen recognized by skin-reactive Treg cells, we are able to enhance skin-specific tTreg cell generation using three approaches. First, we increase medullary thymic epithelial cells by using mice lacking osteoprotegerin or by adding TRANCE (RANKL, Tnfsf11). Second, we inject intrathymically peripheral dendritic cells from skindraining sites. Finally, we inject skin tissue lysates intrathymically. These findings have implications for enhancing the generation of organ-specific Treg cells in autoimmune diseases.